Bond Strength and Reactivity Scales for Lewis Superacid Adducts: A Comparative Study with In(OTf)3 and Al(OTf)3. Issue 6 (6th February 2017) - Compain, Guillaume; Sikk, Lauri; Massi, Lionel; Gal, Jean‐François; Duñach, Elisabet
Abstract: Metal triflates, often called Lewis superacids, are potent catalysts for organic synthesis. However, the reactivity of a given Lewis superacid toward a given base is difficult to anticipate. A systematic screening of catalysts is often necessary when developing synthetic methodologies. Presented herein is the development of quantitative reactivity and bond strength scales by using mass spectrometry (MS). By applying a collision‐induced dissociation (CID) technique to the adducts formed between Lewis superacids Al(OTf)3 or In(OTf)3 with a series of amides bases, including monodentate and bidentate ligands, different dissociation pathways were observed. Quantitative relative energy scales were established by performing energy‐resolved mass spectrometry (ERMS) analysis on the adducts. ERMS of the adducts affords a bond strength scale when the fragmentation leads to the loss of a ligand, and reactivity scales when the dissociation leads to the C−F bond activation of one triflate anion or the deprotonation of the ligand. Al(OTf)3 was found to bind stronger to amides than In(OTf)3 and to provide the most reactive adducts. Abstract : Study of isolated cations ! Dissociation of a series of Lewis superacid adducts formed with amide ligands by variable‐energy collision‐induced dissociation allows the emergence of new quantitative scales to investigate the reactivity and the bond strength of Lewis superacids toward Lewis bases (ligands or substrates). This methodology affords a powerful tool for the comprehensive understanding of the reactivity of Lewis superacids.